Investigation of the Effects of Different Activation Techniques on the Penetration and Distribution of Novel Nanoparticle-Based Irrigants Within the Root Canal System - R Ambika Kumari; CK Vipin; Palanisamy Nandhini; Rohit Vadlamani; Krutika Kadam; Sabari Murugesan (Journal of Pharmacy and Bioallied Sciences)
Background and Objective: This study investigated the effects of different activation techniques on the penetration and distribution of nanoparticle-based irrigants in root canals. Materials and Methods: Forty-five extracted mandibular premolars were divided into three groups: conventional syringe irrigation (control), ultrasonic activation, and laser activation, each using silver nanoparticles. Confocal laser scanning microscopy and Image J software analyzed penetration depth. Results: The mean penetration depths of 2.79 mm (control), 6.58 mm (laser), and 5.37 mm (ultrasonic). Welch’s one-way ANOVA revealed significant differences (P < 0.001), with laser activation achieving the greatest penetration. Conclusion: Laser activation of AgNPs enhances root canal disinfection compared to other methods.